The Kenya Agricultural Commodity Exchange - Okolla, Abraham W. (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Kenya Agricultural Commodity Exchange (KACE) supplies reliable and timely information on the availability and prices of a wide range of commodities, and links buyers and sellers in domestic and global markets